LOST RELICS: PROBLEM OF PRESERVATION OF MONUMENTS OF ARCHITECTURE AND HISTORICAL LOOK OF KURSK - Dorodnykh, Anna Alekseevna (Journal of Applied Engineering Science, 2017)
The article will consider the important problem of preservation and usage of historical and cultural heritage, observe the researches on the history of architecture, contemplate objects of landscape gardening architecture, conditions for their advent and development in the historical center of Kursk. Description of valuable architecture objects under the conditions of urban environment is provided. The research is pointed at modernization of the approach for reconstruction of the most valuable monuments of architecture in Kursk and serves as the base for practical activity — reconstruction of historical and architecture heritage objects in historical center of the city.
Keywords: Architecture relic; Historical look of the city; Historical and architecture heritage; Restoration; Reconstruction